TOURISM DEVELOPMENT STRATEGY BASED ON ENVIRONMENTAL SERVICES WITH INTEGRATED COASTAL ZONE MANAGEMENT (ICZM) TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS (SDGS) IN JOLOSUTRO BEACH OF BLITAR REGENCY INDONESIA - SUMARMI; Listyo Yudha IRAWAN; Dicky ARINTA; Agung SUPRIANTO; Elya KURNIAWATI; Helga Graciani HIDAJAT; MARLINA; Noraindah Binti Abdullah FAHIM; Mohamad ARIF; Adellia Wardatus SHOLEHA; Natasya SHAHERANI (Geo Journal of Tourism and Geosites)
Tourism has become an alternative to improve community welfare. One activity trend is tourism based on an environmental services economy. The aim of this research is to design a tourism development strategy for Jolosutro Beach based on Environmental Services Economics with Integrated Coastal Zone Management (ICZM). This research uses a mixed design (mixed-method design) with a quantitative and qualitative approach. Data were analyzed using suitability analysis for tourism, SWOT, and Huberman interaction analysis. The research results show that the condition of Jolosutro Beach can be developed as environmental services-based tourism with Integrated Coastal Zone Management (ICZM).